Bank liquidity management, prudential regulation, and monetary and exchange rate policy : a re-appraisal of the liquid asset requirement - Singh, Thomas Bissessar ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Argues that trends in liquidity management are optimal, given the presence of risk (or the incompleteness of markets) and commercial banks' limited capacity to manage risk, imperfect competition, and policy induced constraints